Dysregulation of epithelial ion transport and neurochemical changes in the colon of a parkinsonian primate - Erika Coletto (Nature Portfolio, 2021)
Abstract The pathological changes underlying gastrointestinal (GI) dysfunction in Parkinson’s disease (PD) are poorly understood and the symptoms remain inadequately treated. In this study we compared the functional and neurochemical changes in the enteric nervous system in the colon of adult, L-DOPA-responsive, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated common marmoset, with naïve controls. Measurement of mucosal vectorial ion transport, spontaneous longitudinal smooth muscle activity and immunohistochemical assessment of intrinsic innervation were each performed in discrete colonic regions of naïve and MPTP-treated marmosets. The basal short circuit current (I sc) was lower in MPTP-treated colonic mucosa while mucosal resistance was unchanged. There was no difference in basal cholinergic tone, however, there was an increased excitatory cholinergic response in MPTP-treated tissues when NOS was blocked with L-Nω-nitroarginine. The amplitude and frequency of spontaneous contractions in longitudinal smooth muscle as well as carbachol-evoked post-junctional contractile responses were unaltered, despite a decrease in choline acetyltransferase and an increase in the vasoactive intestinal polypeptide neuron numbers per ganglion in the proximal colon. There was a low-level inflammation in the proximal but not the distal colon accompanied by a change in α-synuclein immunoreactivity. This study suggests that MPTP treatment produces long-term alterations in colonic mucosal function associated with amplified muscarinic mucosal activity but decreased cholinergic innervation in myenteric plexi and increased nitrergic enteric neurotransmission. This suggests that long-term changes in either central or peripheral dopaminergic neurotransmission may lead to adaptive changes in colonic function resulting in alterations in ion transport across mucosal epithelia that may result in GI dysfunction in PD.